Association of ABO and Rh Blood Group Phenotypes with Type 2 Diabetes Mellitus at Felege Hiwot Comprehensive Referral Hospital Bahir Dar, Northwest Ethiopia. (6th November 2020) - Legese, Biruk; Abebe, Molla; Fasil, Alebachew
Abstract : Background . ABO and Rh blood group antigens are thought to be among genetic determinants of type 2 diabetes mellitus. Identification of blood group phenotypes are more associated with type 2 diabetes mellitus. It will be helpful for individuals who are susceptible blood groups to take care of themselves by avoiding other predisposing factors and taking preventive measures. Methods . Hospital-based comparative cross-sectional study was carried out from February to April 2019 at Felege Hiwot Comprehensive Referral Hospital. Sociodemographic and clinical data were collected with a semistructured pretested questionnaire. ABO and Rh Blood group were determined by slide and test tube methods. Biochemical parameters were determined with Mindray BS-200E fully automated clinical chemistry analyzer. Data were analyzed by IBM SPSS version 20 statistical software. Chi-square test and logistic regression analysis were employed for data analysis. A P value of < 0.05 was considered statistically significant. Results . From a total of 424 participants included for this study, blood group O was found higher in frequency with 74 (34.9%) and 97 (45.75%) for cases and healthy controls, respectively. ABO blood groups showed significant association with T2DM, a chi-square value of 12.163 and P value of 0.007. However, the Rh blood group was not associated with T2DM. Binary logistic regression analysis revealed that blood group B had a higher risk (OR: 2.12, 95% CI: 1.33-3.32) and blood group O had decreased risk (OR: 0.636, 95% CI: 0.43-0.94) of T2DM as compared to other blood groups. Conclusion . ABO blood group antigens showed significant association with type 2 diabetes mellitus. Blood group B was associated with an increased risk and O blood group with decreased risk of type 2 diabetes mellitus.